Use of acids as additives in sugarcane silage - van Cleef, Eric H. C. B. [UNESP]; Rego, Anibal C.; Patino, Rene M.; Scarpino van Cleef, Flavia O. [UNESP]; Ezequiel, Jane M. B. [UNESP] (Univ Antioquia, Fac Ciencias Agrarias, 2015)
Background: sugarcane silage often becomes a problem for the producers due to its high population of yeast and its high content of soluble carbohydrates. Objective: to evaluate the effect of formic and phosphoric acid on the chemical composition, fermentation characteristics, and digestibility of sugarcane silages. Methods: sugarcane was ensiled in experimental mini-silos. Five treatments were evaluated in the ensilage process (sugarcane added with 0.5 or 1% formic acid and 0.5 or 1% phosphoric acid, and a control treatment without additives). A completely randomized design was used. Results: the dry matter content of silages containing phosphoric acid was lower. Lower values of NDF, ADF, and hemicellulose were observed in the control and formic acid treatments. Conclusions: formic and phosphoric acids promote beneficial changes in the chemical composition of sugar cane silage.
Keywords: forages; formic acid; phosphoric acid; Saccharum officinarum